1982
DOI: 10.2337/diacare.5.5.466
|View full text |Cite
|
Sign up to set email alerts
|

A crossover comparison of continuous subcutaneous insulin infusion (CSII) against multiple insulin injections in insulin-dependent diabetic subjects: improved control with CSII

Abstract: Ten insulin-dependent C-peptide-negative diabetic subjects, whose control had been optimized on twice-daily injection therapy, were treated for periods of 10 wk in a crossover study, with either a thrice-daily subcutaneous insulin injection regimen (Actrapid + Ultratard) or by continuous subcutaneous insulin infusion (CSII). On CSII insulin dose stabilized at 51 +/- 5 U/day, compared with 80 +/- 9 U/day (P = 0.004) on the thrice-daily injection regimen, having been 60 +/- 6 U/day on twice-daily therapy. After … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
25
0
1

Year Published

1984
1984
2010
2010

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 72 publications
(31 citation statements)
references
References 0 publications
1
25
0
1
Order By: Relevance
“…In seven [13,19,22,30,35,36,39] of these investigations, the difference was statistically significant. One study [20] did not find any difference between the treatment groups and another [16] showed insulin requirements to be higher under pump therapy, but without statistical significance.…”
Section: Total Insulin Requirementsmentioning
confidence: 86%
See 3 more Smart Citations
“…In seven [13,19,22,30,35,36,39] of these investigations, the difference was statistically significant. One study [20] did not find any difference between the treatment groups and another [16] showed insulin requirements to be higher under pump therapy, but without statistical significance.…”
Section: Total Insulin Requirementsmentioning
confidence: 86%
“…Adult patients with type 1 diabetes mellitus Of 14 studies reporting total insulin requirements at the end of treatment, 12 [13,19,22,24,28,30,[33][34][35][36][37]39] consistently found that the insulin doses were lower in CSII-treated patients. In seven [13,19,22,30,35,36,39] of these investigations, the difference was statistically significant.…”
Section: Total Insulin Requirementsmentioning
confidence: 99%
See 2 more Smart Citations
“…As a result a series of studies addressed the question of whether multiple injection therapy had the same potential as continuous subcutaneous insulin infusion for improving blood glucose control [9][10][11]. In designing these studies the authors adopted to a greater or lesser degree some of the principles that have since become enshrined as components of intensive therapy, in particular as applied to the various studies of the effect of tight control on the evolution of microvascular complications.…”
mentioning
confidence: 99%